State Governance in Hadith: A Comprehensive Examination of á¹¢ahifah Madinah - Hemawati, Hemawati; Anwar Umar Harahap, Khoirul (Diroyah : Jurnal Studi Ilmu Hadis, 2023)
The á¹¢ahifah Madinah stands as a classical document regarded as the cornerstone of governance during the era of Prophet Muhammad SAWin Madinah. Functioning as a compass for statecraft, it undeniably constitutes a focal point in the realm of hadith studies, encompassing a plethora of concepts intertwined with the fundamentals of state governance. This study seeks to elucidate the principles of state governance embedded within the á¹¢ahifah Madinah. Employing an interdisciplinary approach that merges the realms of hadith studies, history, and political science, this research is underpinned by a library-based methodology and involves a rigorous content analysis of the hadiths encapsulated within the á¹¢ahifah Madinah. The findings of this investigation unveil the presence of hadiths pertinent to the á¹¢ahifah Madinah across several canonical collections. Notably, Sahih al-Bukhari contains hadiths bearing numbers 7300, 1870, 3172, 3179, 6755, and 1366. Similarly, Sahih Muslim presents hadiths denoted by numbers 1366, 1370, 1371, 1372, 1373, and 3179. Furthermore, Sunan Abu Daud encompasses hadiths numbered 3000 and 2034, while Musnad Imam Ahmad hosts hadiths bearing numbers 615, 959, 1040, 1231, 1873, 8808, 9432, 10424, 13087, 13540, and 362. Lastly, Sunan at-Tirmidzi includes hadith number 2127 as part of this discourse. Consequently, this research identifies a spectrum of key principles germane to state governance. These encompass the principles of integrity, compliance, equity, deliberation, egalitarianism, solidarity, liberty, acknowledgment, and safeguarding of human rights, an impartial judiciary, the promotion of peace, and the advancement of collective well-being